The Influence of Profitability, Solvency and Company Age on Audit Report Lag in Mining Sector Companies Listed on the IDX (Period 2020 – 2022) - Aryani, Anggi Oktavia; As’ari, Hasim (CV. Rayyan Dwi Bharata, 2024)
This research aims to analyze and obtain empirical evidence regarding the influence of profitability, solvency and company age on audit report lag. The type of data used in this research is secondary data in the form of the company's annual financial report. The research population is mining sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique used purposive sampling, resulting in a total research sample of 30 companies. The research method uses multiple linear regression analysis. The results of this research show that profitability, solvency and company age simultaneously influence audit report lag. Then, partially, solvency and company age have no effect, but profitability has a negative effect on audit report lag. Research findings show that the average audit report lag is 89 days after book closing.